Advances in the Isolation of Specific Monoclonal Rabbit Antibodies - Zhang, Zaibao; Liu, Huijuan; Guan, Qian; Wang, Lei; Yuan, Hongyu (Frontiers in Immunology, 2017)
The rabbit monoclonal antibodies (mAbs) have advantages in pharmaceuticals and diagnostics with high affinity and specificity. During the past decade, many techniques have been developed for isolating rabbit mAbs, including single B cell antibody technologies. This review describes the basic characterization of rabbit antibody repertoire and summarizes methods of hybridoma technologies, phage display platform, and single B cell antibody technologies. With advances in antibody function and repertoire analysis, rabbit mAbs will be widely used in therapeutic applications in the coming years.